Circulation and control : artistic culture and intellectual property in the nineteenth century - Delamaire, Marie-Stéphanie; Slauter, Will, 1977- (Open Book Publishers, 2021)
With contributions by art historians, legal scholars, historians of publishing, and specialists of painting, photography, sculpture, and graphic arts, this rich collection of essays explores the relationship between intellectual property laws and the cultural, economic, and technological factors that transformed the pictorial landscape during the nineteenth century.